THE ROLE OF ART IN CREATING EMPATHY FOR NATURE - Pulsinelli, Gabryella Marie (Wake Forest University, 2019)
My investigation in this thesis explores how environmental art has the potential to
Keywords: Art; Environmental art; nature; Photography